Differential roles of miR‐15a/16‐1 and miR‐497/195 clusters in immune cell development and homeostasis - Hutter, Katharina (FEBS J, 2020)
MicroRNAs (miRNAs) post‐transcriptionally repress almost all genes in mammals and thereby form an additional layer of gene regulation. As such, miRNAs impact on nearly every physiological process and have also been associated with cancer. Prominent examples of such miRNAs can be found in the miR‐15 family, composed of the bicistronic clusters miR‐15a/16‐1, miR‐15b/16‐2, and miR‐497/195. In particular, the miR‐15a/16‐1 cluster is deleted in almost two thirds of all chronic B lymphocytic leukemia (CLL) cases, a phenotype that is also recapitulated by miR‐15a/16‐1‐deficient as well as miR‐15b/16‐2‐deficient mice. Under physiological conditions, those two clusters have been implicated in T‐cell function, and B‐cell and natural killer (NK) cell development; however, it is unclear whether miR‐497 and miR‐195 confer similar roles in health and disease. Here, we have generated a conditional mouse model for tissue‐specific deletion of miR‐497 and miR‐195. While mice lacking miR‐15a/16‐1 in the hematopoietic compartment developed clear signs of CLL over time, aging mice deficient for miR‐497/195 did not show such a phenotype. Likewise, loss of miR‐15a/16‐1 impaired NK and early B‐cell development, whereas miR‐497/195 was dispensable for these processes. In fact, a detailed analysis of miR‐497/195‐deficient mice did not reveal any effect on steady‐state hematopoiesis or immune cell function. Unexpectedly, even whole‐body deletion of the cluster was well‐tolerated and had no obvious impact on embryonic development or healthy life span. Therefore, we postulate that the miR‐497/195 cluster is redundant to its paralog clusters or that its functional relevance is restricted to certain physiological and pathological conditions.